Müller cells and astrocytes in tractional macular disorders. (January 2022) - Bringmann, Andreas; Unterlauft, Jan Darius; Barth, Thomas; Wiedemann, Renate; Rehak, Matus; Wiedemann, Peter
Abstract: Tractional deformations of the fovea mainly arise from an anomalous posterior vitreous detachment and contraction of epiretinal membranes, and also occur in eyes with cystoid macular edema or high myopia. Traction to the fovea may cause partial- and full-thickness macular defects. Partial-thickness defects are foveal pseudocysts, macular pseudoholes, and tractional, degenerative, and outer lamellar holes. The morphology of the foveal defects can be partly explained by the shape of Müller cells and the location of tissue layer interfaces of low mechanical stability. Because Müller cells and astrocytes provide the structural scaffold of the fovea, they are active players in mediating tractional alterations of the fovea, in protecting the fovea from such alterations, and in the regeneration of the foveal structure. Tractional and degenerative lamellar holes are characterized by a disruption of the Müller cell cone in the foveola. After detachment or disruption of the cone, Müller cells of the foveal walls support the structural stability of the foveal center. After tractional elevation of the inner layers of the foveal walls, possibly resulting in foveoschisis, Müller cells transmit tractional forces from the inner to the outer retina leading to central photoreceptor layer defects and a detachment of the neuroretina from the retinal pigment epithelium. This mechanism plays a role in the widening of outer lameller and full-thickness macular holes, and contributes to visual impairment in eyes with macular disorders caused by conractile epiretinal membranes. Müller cells of the foveal walls may seal holes in the outer fovea and mediate the regeneration of the fovea after closure of full-thickness holes. The latter is mediated by the formation of temporary glial scars whereas persistent glial scars impede regular foveal regeneration. Further research is required to improve our understanding of the roles of glial cells in the pathogenesis and healing of tractional macular disorders.